ANALISIS PENERAPAN KEPEMIMPINAN MULTIKULTURAL DALAM MENGELOLA GURU EKSPATRIAT DI SMP TRILINGUAL PAH TSUNG CENGKARENG - Dede Aminudin; Nuryati Djihadah; Neng Nurhemah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze in depth the implementation of the principal's multicultural leadership in managing expatriate teachers at Pah Tsung Trilingual Junior High School, Cengkareng. A qualitative approach with a case study method was employed. The primary data sources were obtained from the school principal and expatriate teachers as key informants who provided accurate information. Data collection was comprehensively conducted through interviews, observations, and document analysis. Data analysis was performed interactively and continuously using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing/verification until data saturation was reached. The research findings reveal four main points: First, the principal implements transformative leadership with high cognitive flexibility by adapting specific communication styles (high-context for Asian teachers and low-context for Western teachers). Second, the integration strategy is executed through an integrated workspace layout without nationality boundaries to trigger organic knowledge sharing and dismantle psychological barriers. Third, the mitigation of culture shock and pedagogical clash is proactively managed through a "bridging the gap" strategy by publishing a specific handbook and aligning different grading orientations (process vs. outcome). Fourth, the principal effectively acts as a cultural broker, emphasizing neutrality and dialectical mediation to create organizational justice, thereby fostering a feeling of being respected that enhances the loyalty and professional performance of expatriate teachers. This study concludes that adaptive, structural, and theoretical multicultural leadership is the key to successful foreign educator management in a trilingual school.